Antioxidant properties of HDL: beyond cardiovascular protection - Zeljković, Aleksandra; Vekić, Jelena; Kotur-Stevuljević, Jelena; Stefanović, Aleksandra; Mihajlović, Marija (Archives of Pharmacy, 2022)
High-density lipoprotein (HDL) is the most complex lipoprotein particle, containing lipids and dozens of various functional proteins. Such sophisticated composition enables numerous activities of HDL; from the reverse cholesterol transport, to antioxidative, anti-inflammatory, anti-aggregation, antiadhesive, and vasodilatory effects. Accordingly, the significance of HDL goes far beyond its cardioprotective properties and novel research points towards its role in etiopathogenesis of various other diseases. Antioxidative properties of HDL are primarily attributed to the enzyme paraoxonase 1 (PON1), whose principal role is to protect low-density lipoprotein (LDL) and cell membranes against harmful effects of reactive oxygen species. PON1 is located on HDL particles and its activity largely depends on HDL structure. Our investigations have shown that PON1 is not equally distributed across the entire population of serum HDL subfractions. Namely, our results suggest that the allocation of PON1 on specific HDL subclasses changes in pathophysiological conditions, such as chronic kidney disease, polycystic ovary syndrome, or hypertension in pregnancy. Similarly, a shift in HDL subclasses distribution toward smaller, dysfunctional particles is reported in diabetes, metabolic syndrome, obstructive sleep apnea, sarcoidosis, but also in malignant diseases, such as colorectal cancer. In parallel, antioxidative defense mechanisms were diminished in all these categories of patients, which was evident as decreased PON1 activity and rise of oxidative stress. Structural modifications of HDL particles affect their functions, thus antioxidative capability of PON1 depends on qualitative properties of its lipoprotein carrier. Such complex interaction is highly significant for the initiation and progression of numerous diseases.